PENGEMBANGAN E-MODUL FISIKA BERBASIS STEM DENGAN PRINSIP PEMBANGUNAN BERKELANJUTAN TERHADAP LITERASI SAINS SISWA KELAS XI - Vira Kiswanda; Prima Aswirna; Nurhasnah Nurhasnah (UIN Imam Bonjol Padang, 2022)
Scientific literacy of students are classified as low because there are no educational material is to form scientific literacy and environmentally friendly attitudes using”principles of sustainable development goals.””It’s purpose”of this research to produce a STEM-based physics e-Module with the principle of sustainable development of scientific literacy for class XI students differences”valid, practical, and effective. This research is research and development (R&D) using the Plomp model and consists of the following three phases:”1) preliminary research 2) prototype development and 3) assessment phase. The STEM-based e-Module use principle of developments according to the laws of thermodynamics and global warming are highly relevant,”verage score of 83.72% with percent validity”studies 77.77% language eligibility 92% and media eligibility 81.4%. The practicality of teachers is 86.66% and students are 85.66% in the very practical category. Efficiency is classified as very effective of 89.5% female students and 88.7% male students.”Scientific literacy test results”for women 82% and men 81% were categorized as very effective.’Based on these results, it can be concluded that the STEM based physics e-Module with the principle of sustainable development on scientific literacy for class XI students is very valid, practical, and effective’.